Oral Corrective Feedback on Student's Writing in Secondary EFL Classroom (RETAIN, 2020)
Corrective feedback which purposes to assist teacher and student towards the error both in English language learning as second and foreign language is widely gave in language teaching and learning. The current study focused on describing corrective feedback on spoken form on student’s writing in secondary EFL classroom. The researcher also described the kinds of oral corrective feedback that given by the teacher and student’s responses towards corrective feedback orally. Basic interpretative study research design is used and the subject of the study were 36 EFL student in one of secondary Indonesian classroom. The researcher used two instruments which were field notes and video recording as the supplementary instrument to answer the first two research questions followed by two other instruments to answer the last research question, they were questionnaire and interview. The result showed that the teacher gave oral corrective feedback to correct student’s error on writing using two kinds, namely clarification request and metalinguistic feedback. In addition, the students were also interested in receiving feedback orally to assist them in improving the errors. Keywords: oral corrective feedback, student’s writing, secondary EFL classroom.